Evolutionary and comparative genomics of leptospira - DOI: 10.3395/reciis.v1i2.Sup.103en - Natalia Rego; Hugo Naya; Guillermo Lamolle; Fernando Alvarez-Valin (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2007)
The availability of complete genome sequences has allowed the study of genic and nucleotide content changes during the evolution of pathogenic and symbiont bacterial lineages. Here we present the comparative genomics between four strains belonging to two species, Leptospira interrogans (L.interrogans Lai str. 56601 and L. interrogans Copenhageni str. Fiocruz L1-130) and L. borgpetersenii (L. borgpetersenii serovar Hardjo-bovis str. JB197 and L. borgpetersenii serovar Hardjo-bovis str. L550). Strains from the latter species have reduced their host range being restricted to a host-to-host transmission cycle while the former species could survive for long periods in fresh water. A detailed compositional and substitutional analysis of 2416 tetrads of orthologs indicates that this change in environmental condition is accompanied by changes in genomic GC content that affected the entire genome. Moreover, this analysis reveals that the interspecies divergence is surprisingly large, with a synonymous/amino acid distances ratio equal to 7.17, a ratio much larger than in other groups. We show that this increased ratio is an indication of acceleration in substitutions rates that especially affected synonymous positions and is in connection with the change in base composition already described. We hypothesize that this process specifically took place in the branch that leads to L. borgpetersenii.